Reaction Pathway and Free Energy Profile for Butyrylcholinesterase-Catalyzed Hydrolysis of Acetylcholine - Chen, Xi (2010)
Catalytic mechanism for butyrylcholineserase (BChE)-catalyzed hydrolysis of acetylcholine (ACh) has been studied by performing pseudobond first-principles quantum mechanical/molecular mechanical-free energy (QM/MM-FE) calculations on both acylation and deacylation of BChE. It has been shown that the acylation with ACh includes two reaction steps including the nucleophilic attack on the carbonyl carbon of ACh and the dissociation of choline ester. The deacylation stage includes nucleophilic attack of a water molecule on the carboxyl carbon of substrate and dissociation between the carboxyl carbon of substrate and hydroxyl oxygen of Ser198 side chain. Notably, despite of the fact that acetylcholinesterase (AChE) and BChE are very similar enzymes, the acylation of BChE with ACh is rate-determining, which is remarkably different from AChE-catalyzed hydrolysis of ACh in which the deacylation is rate-determining. The computational prediction is consistent with available experimental kinetic data. The overall free energy barrier calculated for BChE-catalyzed hydrolysis of ACh is 13.8 kcal/mol, which is in good agreement with experimentally-derived activation free energy of 13.3 kcal/mol.